Integrable WZNW models and string models of WZNW model type with constant SU(2) torsion - Gershun, V.D. (Вопросы атомной науки и техники, 2012)
The integrability of WZNW model and string model of WZNW model type with constant SU(2) torsion is investigated. The closed boson string model in the background gravity and antisymmetric B-field is considered as integrable system in terms of initial chiral currents. The model is considered under assumption that internal torsion related with metric of Riemann-Cartan space and external torsion related with antisymmetric B-field are (anti)coincident. New equation of motion and exact solution of this equation was obtained for string model with constant SU(2) torsion. New equations of motion and new Poisson brackets (PB) for infinite dimensional hydrodynamic chains was obtained for string model with constant SU(n), SO(n), SP(n) torsion for n → ∞. Исследована интегрируемость ВЗНВ-модели и струнной модели ВЗНВ-типа с постоянным SU(2)-кручением. Замкнутая бозонная струна во внешних гравитационном и антисимметричном полях рассмотрена как интегрируемая система в терминах начальных киральных токов. Модель рассмотрена в предположении, что внутреннее кручение, связанное с метрикой Римана-Kартана пространства, и внешнее кручение, связанное с антисимметричным В-полем, (анти)совпадают. Для модели струны с постоянным SU(2)-кручением получено новое уравнения движения и найдено точное решение в виде функции Ламберта. Для модели струны с постоянным SU(n)-, SO(n)-, SP(n)-кручением для n → ∞ получены новые уравнения движения для бесконечномерных гидродинамических цепочек и новые скобки Пуассона. Досліджена інтегрованість ВЗНВ-моделі та струнної моделі ВЗНВ-типу с постійним SU(2)-скрутом. Замкнута бозонна струна в зовнішніх гравітаційному и антисиметричному полях розглянута як інтегрована система у термінах первісних кіральних струмів. Модель розглянута за припущенням що внутрішній скрут, зв'язаний з метрикою Рімана-Картана простору, та зовнішній скрут, зв'язаний з антисиметричним В-полем, (анти)співпадають. Для моделі струни з постійним SU(2)-скрутом одержано нове рівняння руху та знайдені точні рішення у вигляді функції Ламберта. Для моделі струни з постійним SU(n)-, SO(n)-, SP(n)-скрутом з n → ∞ одержані нові рівняння руху для нескінченновимірних гідродинамічних ланцюгів та нові дужки Пуассона.